A comprehensive study on minimum quantity lubrication. (2022) - Kumar, Santosh; Kumar, Rakesh; Singh, Swarn; Singh, Harvinder; Kumar, Amresh; Goyal, Rachin; Singh, Sham
Abstract: The cutting fluid plays a significant role by cooling the surface of tool, substrate and removing chips from the cutting area during metal machining operations (turning, milling, grinding etc.). However, by adopting the conventional method of cooling (flood cooling), it affects the human health and the environment badly. In addition, it accounts for 16–20% of the total cost of manufacturing in the production industry. To overcome this issue, minimum quantity lubrication (MQL) is gaining higher potential for attaining good quality surface and improved overall performance of machining than conventional cooling methods. Because MQL system reduce the use of coolant by depositing the suitable mixture of cutting fluid and compressed air during machining in optimum quantity. In general the amount of cutting fluid in MQL system is in ml/hr instead of in l/min as in flood cooling. Beside these benefits of MQL system, it also decreases the cutting forces, tool wear, temperature and friction during machining. Hence the aim of this paper is to provide an overview of MQL system, cutting fluids and effect of MQL on the machining performance during turning operation. The study revealed that by employing MQL system in turning results in significant enhancement in metal removal rate and surface finish by 30% and reduced cutting force (by 17.07–40%), cutting temperature (by 6.72–10%), tool wear and eliminated built up edge. Overall this improved the overall performance of the machining.